2021
DOI: 10.5005/jp-journals-10071-23875
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Changes in PPV Using a Tidal Volume Challenge with a Passive Leg Raising Test to Predict Fluid Responsiveness in Patients Ventilated Using Low Tidal Volume

Abstract: A bstract Background Tidal volume challenge pulse pressure variation (TVC-PPV) is considered one of the recent reliable dynamic indices of fluid responsiveness (FR); also, passive leg raising (PLR)-induced changes in cardiac output (CO) detected by echocardiography are considered a reliable reversible self-fluid challenge test; many patients share eligibility for both tests. Objectives The study aimed to compare the sensitivity and specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The black diamond squares represent percentage change of pulse pressure variation (△PPV%). The cutoff values of △PPV are as follows: (1) Myatra 2017 [ 14 ], 3.5%; (2) Jun 2019 [ 16 ], 1%; (3) Elsayed 2021 [ 19 ], 3.5%; (4) Taccheri 2021 [ 20 ], 1%; Hamzaoui2021 [ 21 ]; (5) Shi 2022 [ 22 ], 3.5%; (6) Xu 2022 [ 23 ], 2%. The cutoff values of △PPV% are as follows: (1) Myatra 2017 [ 14 ], 48%; (2)Yonis 2017 [ 15 ], 29%; (3) Jun 2019 [ 16 ], 25%; (4) Messina 2019 [ 17 ], 13.3%; (5) Messina 2020 [ 18 ], 12%; (6) Taccheri 2021 [ 20 ], 20%; …”
Section: Resultsmentioning
confidence: 99%
“…The black diamond squares represent percentage change of pulse pressure variation (△PPV%). The cutoff values of △PPV are as follows: (1) Myatra 2017 [ 14 ], 3.5%; (2) Jun 2019 [ 16 ], 1%; (3) Elsayed 2021 [ 19 ], 3.5%; (4) Taccheri 2021 [ 20 ], 1%; Hamzaoui2021 [ 21 ]; (5) Shi 2022 [ 22 ], 3.5%; (6) Xu 2022 [ 23 ], 2%. The cutoff values of △PPV% are as follows: (1) Myatra 2017 [ 14 ], 48%; (2)Yonis 2017 [ 15 ], 29%; (3) Jun 2019 [ 16 ], 25%; (4) Messina 2019 [ 17 ], 13.3%; (5) Messina 2020 [ 18 ], 12%; (6) Taccheri 2021 [ 20 ], 20%; …”
Section: Resultsmentioning
confidence: 99%
“…The Vt challenge has been validated by far fewer studies than the PLR test, for example, although its reliability has been confirmed in a recent meta-analysis [ 54 ]. Moreover, the diagnostic thresholds differ slightly between the few available studies (Table 2 ), which in addition expressed the change in PPV either as an absolute value [ 30 , 52 , 65 ]} or as a percent change [ 56 , 66 , 67 ], or both [ 29 ].…”
Section: Tidal Volume Challengementioning
confidence: 99%